RENA PAPASPYROU: AN EXPLORER OF THE URBAN SPACE SINCE THE 1970’ - PANTAZIS, EFSTRATIOS (Design/Arts/Culture, 2026)
Review of the exhibition Rena Papaspyrou: Images Through Matter, at the Hellenic Centre, London (October 2 – November 16, 2024). Curated by Inês Costa, Curator of Focal Point Gallery and Nayia Yiakoumaki, Director of the Hellenic Centre with Grace Strasen, Public Programme & Events Co-ordinator, The Hellenic Centre. The Hellenic Centre, in London, hosts Rena Papaspyrou’s Images Through Matter, her first solo debut exhibition in London and the United Kingdom this autumn. The audience has the opportunity to view and appreciate the work of one of the most important artists of the generation of the 1970s in Greece, and the first woman elected Director of the Third Painting Studio at the Athens School of Fine Arts (1993–2005). Her artistic expression involves elements and materials of the urban space, such as wood, metal, mosaic tiles, which until today play a central role in her practice. She explores the possibilities of matter by drawing most of the times on materials connected to the city, such as on wall surfaces that she removes from buildings. She marks and wades in with color and ink on the subtle changes on each surface, projecting simple images that emerge from the existing patterns.